1977
DOI: 10.3109/08860227709037649
|View full text |Cite
|
Sign up to set email alerts
|

Hemofiltration: Treatment of renal Failure by Ultrafiltration and Substitution

Abstract: Hemofiltration, in contrast to hemodialysis or peritoneal dialysis, eliminates toxic substances accumulated in uremia by a process that is independent of molecular weight. By means of a special device, the ultrafiltrate of blood is replaced, up to the desired amount, by a modified Ringer's lactate solution. The application of this new method results in better control of severe hypertension, and controls calcium phosphate and lipid metabolism in a more physiologic manner than dialysis does, without additional d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

1983
1983
2000
2000

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 1 publication
0
10
0
1
Order By: Relevance
“…Similarly, during haemodialysis there is a preferential movement of solute from the extracellular compartment resulting in a greater fall in plasma osmotic pressure [18], which may lead to the passage of water into the intracellular compartment resulting in cerebral oedema, whereas haemofiltration has been reported to result in a reduction in the extracellular volume without any change in the intracellular fluid volume [19].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, during haemodialysis there is a preferential movement of solute from the extracellular compartment resulting in a greater fall in plasma osmotic pressure [18], which may lead to the passage of water into the intracellular compartment resulting in cerebral oedema, whereas haemofiltration has been reported to result in a reduction in the extracellular volume without any change in the intracellular fluid volume [19].…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that, although the urea filtra tion rate and urea clearance were higher in HF than HD to compensate for shorter treat ment time, significantly less hypotension de veloped owing to sodium flux in HF. The incidence of dialysis disequilibrium syn drome is less [1,5]. One of the major causes for dialysis disequilibrium syndrome is rapid changes in solute concentration difference between blood and CSF.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, easy and asymptomatic removal of excess body fluid is possible by HF, leading to better control of hypertensive as well as hypotensive patients. Quellhorst et al [1] and ourselves [5] have postulated that one-way mobilization of body fluid from the intracellular to the extra cellular compartment might occur during HF owing to a smaller decrease in plasma osmo lality. In order to clarify this hypothesis, the kinetics of urea and sodium, which contrib ute greatly to extracellular fluid osmolality, were studied during HD and HF.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Already in the late 1970s, Bergström [3] and Quellhorst et al [4] showed that blood pressure was better maintained when fluid was withdrawn during either isolated ultrafiltration or hemofiltration as compared to combined ultrafiltration hemodialysis. Differences in blood volume preservation due to osmotic changes as well as differences in vascular reactivity due to differences in increase of sympathetic tone has been held responsible for the disparity in blood pressure stability [5,6].…”
Section: Introductionmentioning
confidence: 99%